Continuous realtime monitoring of patient’s vital signs based onzigbee standard - Koceski, Saso; Kotevska, Olivera; Vlahu-Gjorgievska, Elena; Trajkovik, Vladimir (Institute of Advanced Engineering and Science (IAES), 2014)
This paper gives an understanding of what possibilities Wireless Body Area Network (WBAN) have when using shortrange wireless communications protocols. There advantages are used to facilitate versatility in the movements of health care patients. The paper investigates the feasibility of using the ZigBee protocol, givean analysis of methods for collection of received data from multi sensor environment, and mechanisms for privacy and data protection by using encryption techniques. This characteristics are applied on previously developed collaborative healthcare system model (COHESY).COHESY is aimed at continuous real time remote patients’ health monitoring.
Keywords: Data processing, Real time monitoring, Wireless body area network, ZigBee